Meshed Patch Antenna for Portable UHF Band Radio Communication Devices - Artamonovs, Olegs; Balodis, Guntars (Elektronika ir Elektrotechnika, 2015)
This paper presents a meshed microstrip patch antenna for UHF band radio communications. Meshed elements allow making antenna flexible, light and more suitable for wearable devices. Several antennas, intended for PMR446 band with different meshing configurations, have been designed. Un-meshed, semi-meshed and fully meshed microstrip patch antennas have been compared. The analysis was focused on the best tradeoffs between concentration of conductor, gain and front to back ratio. Results below are showing that more than 50 % of conductor can be removed without significant gain reduction. In some cases the meshing gives a reduction of back radiation. The meshed antenna has smaller dimensions in comparison with the unmeshed antenna on the same frequency. DOI: http://dx.doi.org/10.5755/j01.eee.21.4.12778